Sustainable development reports of agricultural enterprises:the methodological framework for accounting and analytical support - SokilО. H. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The research problem of accounting and analytical support for the formation of sustainable development reports by agricultural enterprises is characterized by many important aspects related specifically to accounting, analysis, reporting and standardization. In addition, there is a need to develop a methodological framework for reporting on sustainable development in agricultural sector despite previous fundamental research and synthesis of previous aspects of sustainable development reporting. The purpose of the article is to generalize the theoretical aspects and develop a methodological framework for accounting and analytical support for the formation of sustainable development reports by agricultural enterprises. The global trend in reporting on corporate responsibility by agricultural enterprises is analyzed in the article. It is established that agricultural enterprises in Eurasia and South America were the largest producers of non-financial reports in 2016, which can be explained by the concentration of agriculture in these regions. Of the Ukrainian agricultural enterprises, non-financial reports have been prepared by only three agroconcerns. The main reasons discouraging Ukrainian agricultural producers from making and releasing sustainable development reports are highlighted. Using the hermeneutic method to analyze the sustainable development reporting definition and its alternatives, three options of sustainable development reports of an enterprise are proposed: a report on sustainable development; an alternative report; and an expanded financial report. A matrix for assessing the level of accounting and analytical support for sustainable development of agricultural enterprises has been developed, illustrating the impact of ten sustainable development aspects (strong, essential, insignificant, none) on the accounting and analytical support for the process of generating financial results and their recording in sustainable development reports. A decision tree is built for selecting the options of sustainable development reporting by size of agricultural enterprise, its self-identification and awareness of the impact on the eco-social environment.